Rocker RJ part of broadband study committee - Tubeza, Philip C. (2017)
A Cabinet committee that includes musician RJ Jacinto is reviewing the government's national broadband plan to improve internet speed.
Keywords: Jacinto, Ramon; Internet -- Law and legislation -- Philippines; Esperon, Hermogenes C., Jr; Arroyo, Gloria Macapagal; Philippines. Department of Information and Communications Technology; Andanar, Martin; Salalima, Rodolfo